LB1.61 Prevalence of trichomonas vaginalis among women attending a university clinic in pelotas, brazil using microscopy, culture and the aptima tv assay. (8th July 2017) - Bruni, MP; Silveira, MF; Stauffert, D; Santos, CC; Farias, NAR; Bicca, G; Golparian, D; Unemo, M
Abstract : Introduction: Trichomoniasis is a common sexually transmitted infection caused by the protozoan Trichomonasvaginalis (TV). In Brazil, trichomoniasis is not a reportable infection and the prevalence is underestimated, due to the poor sensitivity of routinely used diagnostic tests. Nucleic acid amplification tests (NAATs) are the most sensitive and specific tests available for TV detection, but TV NAATs are rarely used in Brazil. The objectives of this study were to investigate the prevalence of TV infection and compare the performance of the US FDA-cleared APTIMA TV NAAT (Hologic, San Diego, USA) with wet mount microscopy, Gram stained microscopy and culture for diagnosis of TV infection in women in Pelotas, Brazil. Methods: From August 2015 to December 2016, 499 asymptomatic and symptomatic women attending the Gynaecology and Obstetrics Outpatient Clinic of the Maternal and Child Health Department at the School of Medicine, Federal University of Pelotas, Brazil were enrolled. Vaginal swabs were collected for examination with wet mount and Gram stained microscopy, culture, and Aptima TV assay. The Aptima TV assay was used as gold standard. Results: Participants' mean age was 37 years, the majority were white, had a steady sexual partner and low levels of education. The Aptima TV assay, culture, wet mount microscopy and Gram stained microscopy detected 4.2% (21/499), 2.4% (12/499), 1.2% (6/499), and 0% (0/499), respectively, of women as TV infected. The sensitivity and specificity of wet mount microscopy and culture were 28.57% and 100%, and 57.14% and 99.79%, respectively. The positive predictive value for wet mount microscopy was 100% and negative predictive value was 96.95% while for culture, these values were 92.30% and 98.14%, respectively. Conclusion: Trichomoniasis was prevalent (4.2%) in our population and the routine diagnostic test, wet mount microscopy, had very low (28.6%) sensitivity compared to the Aptima TV NAAT. Improved diagnostic tests and enhanced testing of also asymptomatic patients are crucial to mitigate the transmission of TV infection.